Effect of chord axial stresses on the static strength of cracked tubular T/Y-joints under out-of-plane and in-plane bending. Issue 7 (May 2019) - Li, Tao; Lie, Seng-Tjhen; Cong, Peiwen
This study aims to investigate the strength reduction effect of chord axial stresses on the static strength of cracked tubular T/Y-joints under out-of-plane or in-plane bending moment using finite element analyses. The cracked tubular T/Y-joints contain a semi-elliptical surface crack at the weld toe of the chord. The benchmark analysis compares the numerically computed load–deformation response of a cracked X-joint fabricated from high-strength steel reported in a recent experimental study. This investigation quantifies the strength reduction caused by the chord axial stresses using the chord stress function Qcf . The parametric study covers the effect caused by the variation in both the local crack geometries, that is, the crack area and the global joint dimensions on the computed chord stress function. Finally, we give recommendations to calculate the strength reduction of the investigated cracked joints due to the chord axial stresses.